Selective encryption and optimization based watermarking for robust transmission of landslide images. (October 2021) - Mohan, A.; Anand, A.; Singh, A.K.; Dwivedi, R.; Kumar, B.
Highlights: We develop a robust and secure landslide image watermarking algorithm by using transform-domain scheme. Fusion of PSO and Firefly optimization is used to compute the optimal embedding strength for the embedding of mark data. Selective encryption is considered to enhance the security at low cost. Abstract: In this paper, a secure watermarking algorithm is proposed to efficiently enhance invisibility and robustness simultaneously. First, the combination of transform domain scheme is used to identify the appropriate coefficient for data embedding. To offer a good balance between robustness and invisibility, we computed optimal embedding factors by using the fusion of particle swarm optimisation (PSO) and the Firefly algorithm. Subsequently, the watermark is scrambled by using a step space-filling curve, and the scrambled watermark is embedded into the wavelet domain of the cover image via the optimal embedding factor. Furthermore, selective encryption is applied to the original host image so that the proposed algorithm can also provide an additional level of security at low cost. We achieved average scores of peak signal-to-noise ratio (PSNR), normalised coefficient (NC), number of changing pixel rate (NPCR) and unified averaged changed intensity (UACI) as 55.1471 dB, 0.9956, 0.9801 and 0.3471, respectively. Graphical abstract: Image, graphical abstract